Uncertainty Quantification for Infrasound Propagation in the Atmospheric Environment - Liang Yu; Xiaoquan Yi; Ran Wang; Chenyu Zhang; Tongdong Wang; Xiaopeng Zhang (Applied Sciences, 2022)
The propagation of infrasound in the atmosphere is influenced by atmospheric environmental parameters, which affect the precise localization of the infrasound source. Therefore, it has become crucial to quantify the influence of atmospheric environmental parameters on infrasound propagation. First, in this paper, the tau-p model is chosen as the physical model of infrasound propagation in a non-uniform moving medium. The atmospheric environmental parameters affecting infrasound propagation are determined. Secondly, the atmospheric environmental parameter distribution data are generated using the Sobol sampling method. Third, the generated atmospheric data are incorporated into the physical model of infrasound propagation to solve the output. Finally, Sobol sensitivity analysis is performed for each parameter, and the atmospheric parameter with the largest Sobol index is identified as the one with the most significant influence on infrasound propagation.